PENGEMBANGAN ENSIKLOPEDIA TANAMAN SPERMATOPHYTA PADA RUANG TERBUKA HIJAU KOTA METRO - Siti Nursyifa; Triana Asih; Muhfahroyin Muhfahroyin (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
The aims of this research was to develop on Encyclopedia of Spermatophyta Plants in Green Open Spaces in Metro City. Prodct testing for the benefit of the winder community the feasibility of the encyclopedia is tested by a validatorwho is lecturer at the University of Muhammadiyah Metro. The validation test was carried out by material expert and design expert, and a small group test was carried out. The material expert validation test got a result of 82,7% which means “very feasible” to use. Desaign expert validation test got 90% result which means “very feasible” to use. Small group test got a result 88,9% which means “very feasible” to use. The result of the development of the Spermatophyta plant encyclopedia are very suitable for use in the learning process.